Study on single phase induction motor conditions using voltage level method: article / Mohd Safuan Ali Aspar - Ali Aspar, Mohd Safuan (2010)
This paper presents an analysis of the performance of single phase induction motor (SPIM) by varying the duty cycle of bock chopper. This paper also aims to study the behavior of SPIM characteristics under variable motor conditions. The chopper also has been used to control the voltage input for the single phase isolated gate bipolar transistor (IGBT) bridge inverter. The inverter used PWM technique to supply the motor. The work was conducted by using a digital computer simulation (MATLAB software). In this paper, the simulation results showed the good results of a simple SPIM.